Empowerment of Coastal Communities through Socialization Of Entrepreneurship and MSME Development For The Economic Independence Of Communities, Pontang Sub-District, Serang Regency - Helmi Yazid; Iis Ismawati (EQUATOR SINAR AKADEMIA, 2022)
To increase the economic independence of the people of Domas Village, Pontang District, Serang Regency, it is necessary to conduct socialization on entrepreneurship and the development of MSMEs. The method used in empowerment is active participatory empowerment of mothers and adolescents by transferring knowledge and understanding about ways and strategies for entrepreneurship and developing MSMEs to increase the economic independence of coastal communities through counseling and mentoring. This activity involves Lecturers, Students, Village Government as partners and target groups.